Promising young woman [videorecording (Blu-Ray)] - Fennell, Emerald, 1985-; Mulligan, Carey, 1985-; Burnham, Bo, 1990-; Brie, Alison; Brown, Clancy; Coolidge, Jennifer; Cox, Laverne; Shannon, Molly, 1964-; Britton, Connie; Brody, Adam, 1979- (Universal Pictures Home Entertainment, 2021)
Cassie is wickedly smart, tantalisingly cunning, and she's living a secret double life by night. Now, an unexpected encounter is about to give Cassie a chance to right the wrongs of the past but will jeopardize her future.